(u)Mzantsi Classics Dialogues in Decolonisation from Southern Africa - Masters, Samantha; Nzungu, Imkhitha; Parker, Grant (African Minds, 2022)
Though Graeco-Roman antiquity ('classics') has often been considered the handmaid of colonialism, its various forms have nonetheless endured through many of the continent's decolonising transitions. Southern Africa is no exception. This book canvasses the variety of forms classics has taken in Zimbabwe, Mozambique and especially South Africa, and even the dynamics of transformation itself. How does (u)Mzantsi classics (of southern Africa) look in an era of profound change, whether violent or otherwise? What are its future prospects? Contributors focus on pedagogies, historical consciousness, the creative arts and popular culture. The volume, in its overall shape, responds to the idea of dialogue - in both the Greek form associated with Plato's rendition of Socrates' wisdom and in the African concept of ubuntu. Here are dialogues between scholars, both emerging and established, as well as students - some of whom were directly impacted by the Fallist protests of the late 20-teens. Rather than offering an apologia for classics, these dialogues engage with pressing questions of relevance, identity, change, the canon, and the dynamics of decolonisation and potential recolonisation. The goal is to interrogate classics - the ways it has been taught, studied, perceived, transformed and even lived - from many points of view.